An In-Depth Review of Molecularly Imprinted Electrochemical Sensors as an Innovative Analytical Tool in Water Quality Monitoring: Architecture, Principles, Fabrication, and Applications - Mbuyamba Divin Mukendi; Oluseyi Sikiru Salami; Nomvano Mketo (Micromachines)
Molecularly imprinted electrochemical sensors (MI-ECSs) are a significant advancement in analytical techniques, especially for water quality monitoring (WQM). These sensors utilize molecular imprinting to create polymer matrices that exhibit high specificity and affinity for target analytes. MI-ECSs integrate molecularly imprinted polymers (MIPs) with electrochemical transducers (ECTs), enabling the selective recognition and quantification of contaminants. Their design features template-shaped cavities in the polymer that mimic the functional groups, shapes, and sizes of target analytes, resulting in enhanced binding interactions and improved sensor performance in complex water environments. The fabrication of MI-ECSs involves selecting suitable monomeric units (monomers) and crosslinkers, using a target analyte as a template, polymerizing, and then removing the template to expose the imprinted sites. Advanced methodologies, such as electropolymerization and surface imprinting, are used to enhance their sensitivity and reproducibility. MI-ECSs offer considerable benefits, including high selectivity, low detection limits, rapid response times, and the potential for miniaturization and portability. They effectively assess and detect contaminants, like (toxic) heavy metals (HMs), pesticides, pharmaceuticals, and pathogens, in water systems. Their ability for real-time monitoring makes them essential for ensuring water safety and adhering to regulations. This paper reviews the architecture, principles, and fabrication processes of MI-ECSs as innovative strategies in WQM and their application in detecting emerging contaminants and toxicants (ECs and Ts) across various matrices. These ECs and Ts include organic, inorganic, and biological contaminants, which are mainly anthropogenic in origin and have the potential to pollute water systems. Regarding this, ongoing advancements in MI-ECS technology are expected to further enhance the analytical capabilities and performances of MI-ECSs to broaden their applications in real-time WQM and environmental monitoring.